Project portfolio risk assessment in digital transformation: challenges and opportunities. Issue 1 (October 2021) - Mican, C; Fernandes, G; Araújo, M; Ares, E
Abstract: Digital Transformation (DT) has its own challenges and demands on organizational strategy and processes. Consequently, DT also has implications on Project Portfolio Risk Assessment (PPRA). Thus, this study is focused on identifying these implications based on a structured search and content analysis of the literature in the field, which led to the identification of eight implications for risk assessment. Then, through qualitative analysis and according to the nature of each implication identified, a set of five challenges and three opportunities were established for PPRA considering DT context. This research shows that DT not only demands new considerations for PPRA but also offers opportunities to face them, leading to improve the PPRA impact on project portfolio management decision-making process. The present study contributes to the current PPRA research by outlining a view of how PPRA can be integrated into organizational DT. The challenges and opportunities identified could be used by practitioners and scholars to research, design, and implement PPRA in DT context.